토종자원을 활용한 중생 찰벼 품종 ‘효원3호’ - 권순욱(Soon-Wook Kwon); 임다은(Da-Eun Im); 이주현(Joohyun Lee) (Korean journal of breeding, 2019)
‘Hyowon 3’, a medium-maturing glutinous rice variety was developed by the rice breeding team of Pusan National University in 2013. This cultivar was developed from a cross between ‘Hongna’ which is a landrace from the Korean peninsula showing good glutinous properties, and ‘Junam’, which has stable productivity. During the F3–F8 generations, breeding lines were selected using a pedigree breeding method. As a result, the promising line (JS24-6-95-11-5-2-1-1-1-B) with good glutinous properties was advanced and designated as ‘SP 107’. This variety headed on Aug. 16, which is 3 days later than ‘Dongjinchal’ in the middle plane. The average culm length and panicle length of this variety were 80.7 cm and 20.1 cm, respectively. This variety yielded approximately 14.1 tillers per hill and 104 spikelets per panicle. The ratio of ripened grain was about 93.0%, and the 1,000-grain weight was 19.30 g in brown rice. The yield performance was 492 kg/10a in a local adaptability test. KCI Citation Count: 1